Policy of Development of High-tech in China: Lessons for Ukraine - Salikhova, O. B.; Krekhivskyi, O. V. (Statistics of Ukraine, 2023)
China in the late 1980s, has embarked on a new path of high-tech manufactury development that is in line with its ambitions. The philosophy of China’s innovation and industrial policy is based on the idea that the achievement of competitive manufactury must be through the national high-tech zones and high-tech enterprises, creating new products and processes based on indigenous innovation. The purpose of the study is to to explore the Chinese experience on policy and mechanisms of development of high-tech manufacturies and to analyze of statistical tools to assess its implications; to assess the appropriateness or feasibility of their application in modern economic conditions of Ukraine. The study’s results have enhanced the existing understanding of the effect of State on accelerating the process structural transformation of the economy and its qualitative technological growth. Discovered the fact, that the Chinese Government is providing substantial support in the form of subsidies and tax incentives for establishment of special high-tech zones and high-tech enterprises for encourage the production of new and high-tech products and processes. It was revealed that, in order to grasp the economic operation and scientific, technological, industrial development of high-tech zones and high-tech enterprises, statistical investigation system was specially formulated іn addition to official statistics of the High-tech industries. It is proven that China’s state-led innovation development model has successfully accompanied and stimulated the growth of high-tech over the last 30 years; and has produced numerous endogenous technological innovations. Analysis revealed that considerable efforts in the field of policy of China transforming the industry into a high-tech sector of the economy and a powerful player in the global market have outstanding performance. The article presents the new indicator EVA – coefficient of Comparative Advantages in the Domestic Value Added Exports and formula for its calculation is provided which allow the assessment of the position of China’s high-tech industries, widening the ‘revealed comparative advantage’ concept. This study shows some important conclusions about the determinants of success of the Chinese government in increase of resources for the modernization of industrial technologies, building and strengthening of potential of domestic high-tech manufacturies. It would be advisable to take into account some important levers of influence, following the example of China, when choosing mechanisms for the economic recovery of Ukraine after war.